Contextual Influences on TPACK Mastery and Implementation: A Comparative Study of Teachers in the Philippines and Indonesia - Rania Khairunnisak; Yusuf Tri Herlambang; Tita Mulyati (AL-ISHLAH: Jurnal Pendidikan, 2026)
This study examines differences in Technological Pedagogical Content Knowledge (TPACK) mastery and implementation among teachers in Indonesia and the Philippines, emphasizing the role of contextual and systemic factors. A mixed-methods design was employed to provide a comprehensive analysis of both competencies and practices.A purposive sample of 15 participants, including teachers and school principals involved in technology integration in basic education, was selected. Quantitative data were collected using a validated Likert-scale questionnaire measuring TPACK competencies. Qualitative data were obtained through semi-structured interviews, classroom observations, and document analysis to explore contextual influences on implementation.The results indicate that Filipino teachers demonstrate higher levels of TPACK mastery and more frequent technology integration compared to Indonesian teachers. This difference is associated with sustained professional development, stronger policy support, and more reliable technological infrastructure. Additionally, Filipino educators generally reported longer teaching experience and greater confidence in integrating digital tools. Thematic analysis further revealed that cultural norms, leadership practices, policy enforcement, and resource availability significantly shape TPACK implementation in both contexts.These findings highlight that effective technology integration is not solely determined by individual teacher competence but is strongly influenced by systemic and environmental conditions. The study contributes to the literature by illustrating how contextual factors interact with teacher knowledge to shape instructional practices. It recommends the development of context-sensitive policies and sustained professional development models to enhance TPACK mastery, particularly in resource-constrained settings across Southeast Asia.